Peran Serikat Pekerja dalam mendukung Produktivitas Perusahaan Melalui Hubungan Industrial yang Harmonis - Septian Juliansyah; Silfanny Alvionita; Vina Mardhotillah; Delis Apriyani; Julius Caesar Transon Simorangkir (DPPM Universitas Pelita Bangsa, 2026)
This study aims to analyze the influence of labor unions’ roles on company productivity within the context of Industrial Relations Court (PHI) decisions. Labor unions hold a strategic position as representatives of workers’ interests in advocating for their rights and welfare through mechanisms regulated under Law Number 21 of 2000 concerning Labor Unions. The research employs a normative juridical method with a descriptive-analytical approach, utilizing literature studies, statutory analysis, and examination of relevant PHI decisions. The findings indicate that the active and constructive role of labor unions can positively influence productivity through effective communication, collective bargaining, and participation in tripartite institutions. However, when unions misuse their functions or when industrial relations become disharmonious, negative impacts such as decreased efficiency, conflict, and strikes may occur